Exploring transitions in care from pulmonary rehabilitation to home for persons with chronic obstructive pulmonary disease: A descriptive qualitative study - Jonathan Miranda; Danielle Underwood; Miranda Kuepfer‐Thomas; Drew Coulson; Andy Chansoo Park; Stacey J. Butler; Roger Goldstein; Dina Brooks; Amanda C. Everall; Sara J. T. Guilcher (Wiley, 2020)
Abstract Background Individuals with chronic obstructive pulmonary disease (COPD) often experience high health‐care utilization following pulmonary rehabilitation, suggesting suboptimal transitions to home. Objective To understand the experiences of persons with COPD and health‐care professionals regarding transitions from pulmonary rehabilitation to home, including factors impacting these transitions. Design A descriptive qualitative study. Setting and participants Health‐care professionals working at, and persons with COPD who attended, an inpatient or outpatient pulmonary rehabilitation programme at one large, urban health‐care centre. The centre is located in Ontario, Canada. Main variable studied Experiences of participants with care transitions between pulmonary rehabilitation and home. Semi‐structured interviews were audio‐recorded, transcribed verbatim, and thematically analysed. Results Ten patients and eight health‐care professionals participated. Four main themes were identified around the overall experiences with pulmonary rehabilitation and transitions to home: (a) pulmonary rehabilitation as a safe environment; (b) pulmonary rehabilitation as a highly structured environment; (c) contrasting perceptions of the role of pulmonary rehabilitation; and (d) dependency on pulmonary rehabilitation programmes. Persons with COPD and health‐care professionals identified three key factors that influenced this transition: (a) patients' social support, (b) application of self‐management strategies prior to discharge, and (c) patients' physical and mental health. Conclusion Participants agreed that some patients with COPD experienced suboptimal transitions from pulmonary rehabilitation to home that were characterized by suboptimal self‐management. Further research is needed to develop and evaluate interventions to improve transitions. Such interventions should include strategies to elicit long‐term behaviour change to assist patients when they return into the community.